Examining Whether Risk Factors Influence Student Perceptions of Campus Sexual Violence - Madison Wesenberg; Dakota D. Dickinson; Dana R. Haugen; Katerina Rubachuk; Sandy Jung (Sexual Offending)
The present study examined university students’ perceptions of a campus sexual violence scenario, and specifically determined whether the presence of known risk factors for sexual perpetration would influence their views of an individual who caused harm. Two hundred and seventy-five student participants read a vignette that either included the present or absence of the following three risk factors: Frequent alcohol use, attitudes supportive of rape, and negative peer influence. The findings indicated that the risk factors did not have a significant relationship with students' risk perceptions, indicating that students’ perceptions of risk may not be influenced by the presence of known risk factors. The results suggest that students may use intuition or other non-scientific approaches when assessing instances of interpersonal violence, at least in campus settings. Implications for students, post-secondary institutional safety, and prevention of campus sexual violence are discussed.